Juridical Review of the Civil Dispute Peace Deed Made Before Notary - Aliffianti Putri Irfani; Mohammad Roesli; Ebit Rudianto (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2023)
The purpose of this study was to determine the legal position of a civil dispute settlement agreement and to determine the role of a notary based on position in making a civil dispute settlement agreement. The research method uses descriptive methods to explain, describe, and describe in accordance with the problems that are closely related to this research, and comparative methods to find similarities and differences of opinion by experts to be used as a comparison. The results of the research The legal position of the Peace Deed made before a notary is an authentic deed, which has legal force that can be used as the strongest and most complete evidence. This peace deed guarantees the rights and obligations of the parties for the sake of certainty, order, and legal protection for interested parties in the civil dispute settlement process. Therefore, the peace deed is written evidence, the strongest and most complete and can make a real contribution to dispute resolution quickly and cheaply. The peace deed made before a notary has a legal standing against the court's decision as a complete means of proof and the authority of the notary in making a peace deed as his position as a public official authorized to make authentic deeds, the notary is also authorized to be a mediator as regulated in Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Position of a Notary (hereinafter referred to as the Notary Law) according to the Notary Law a notary may not.